Ki Hadjar Dewantara’s School of Arts Education: A Study of Philosophy on Arts Education Based on Habermas’ Critical Method - Hari Pramono, Koko; Rohendi Rohidi, Tjetjep; Sumaryanto F., Totok; Djatiprambudi, Djuli (The Journal of Educational Development, 2018)
Ki Hadjar Dewantara’s school of arts education: A study of philosophy on arts education based on Habermas’ critical method. There are six steps of critical methods: the empirical analysis of historical philosophy, language analysis, hermeneutics analysis, analysis of ideology criticism, functional analysis, and construction of historical materialism. The research results and discussion show that in this study: (1) Dewantara's art education is defined as an education that is oriented on a system that liberates and instills moral values through arts. (2) The results of the critical analysis: the philosophy of empirical history, language, ideological criticism, functionalism, and historical materialism, in the field of arts education, contain the meaning of selecting the philosophy of applied arts education based on the consciousness of its own cultural basis. (3) In response to the development of human resources, arts education is capable of directing the nation to be superior in the world of science, technology, and arts, based on the fundamental capital of human creativity and cultural manifestations as a source of knowledge. The scientific contributions of this research are as the following. Firstly, in the form of explanatory and ideological analysis and national education and arts education systems through political-socio-cultural explanations. Secondly, the explanation of the ideology of arts education is based on historical, social, political, and cultural bases as a critical study of national and art education practices. Thirdly, the findings of this study are the implications of arts education based on the concept of Dewantara's arts education.